2007
DOI: 10.1111/j.1748-5827.2007.00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Stabilisation of medial shoulder instability by imbrication of the subscapularis muscle tendon of insertion

Abstract: Subscapularis muscle tendon of insertion imbrication is a moderately effective procedure for the management of medial shoulder instability unresponsive to medical and/or arthroscopic management. The angle of abduction of the shoulder was returned to normal in model of medial shoulder instability, following subscapularis muscle tendon of insertion. Subscapularis muscle tendon of insertion imbrication provides a relatively simple method of treating medial shoulder instability in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 18 publications
1
24
0
3
Order By: Relevance
“…Having multiple fixation points might be especially important when suturing damaged tissue. Our technique also included the subscapularis tendon because (1) it is one of the most commonly affected structures in medial shoulder instability and (2) a subscapularis imbrication technique via open approach has been previously described …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Having multiple fixation points might be especially important when suturing damaged tissue. Our technique also included the subscapularis tendon because (1) it is one of the most commonly affected structures in medial shoulder instability and (2) a subscapularis imbrication technique via open approach has been previously described …”
Section: Discussionmentioning
confidence: 99%
“…The medial and lateral glenohumeral ligaments, the joint capsule, and the articular surfaces act as static stabilizers . To maintain shoulder stability, the integrity of the medial glenohumeral ligament (MGHL) and the subscapularis tendon is essential . Franklin et al reported a relative distribution with 78% of the cases presenting with medial, 8% with lateral, and 15% showing a multidirectional instability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, consideration should be given to performing open surgery, repairing torn or stretched structures. Imbrication of the subscapularis tendon of insertion and placement of prosthetic ligaments anchored to anatomic sites of origin and insertion have each been described for the successful management of medial instability of the shoulder joint (Pettitt et al, 2007). Biceps tendon transposition is also a useful and effective technique to restore medial shoulder stability.…”
Section: Arthroscopic Treatment Of Glenohumeral Ligament Insufficiencymentioning
confidence: 99%